Current and Soon-to-Be-Approved Regimens Offer High Cure Rates for HCV - Lederman, Lynne (MD Conference Express, 2014)
A choice of all-oral regimens to treat patients with hepatitis C virus is available in the United States, and more are expected to be approved soon. This article reviews the current regimens and trial data from those that are expected to be approved soon.